Knowledge Accrual Following Participation in Pediatric Fundamental Critical Care Support Course in Gaborone, Botswana*. Issue 8 (August 2018) - Cox, Megan; Afonso, Natasha; Mazhani, Loeto; Kloeck, David; Mysore, Mohan; Roy, Kevin; Setlhare, Segolame; Daman, Tlamelo; Meaney, Peter A.
Abstract : Objectives: To describe provider characteristics, knowledge acquisition, perceived relevance, and instruction quality of the Society of Critical Care Medicine's Pediatric Fundamentals of Critical Care Support course pilot implementation in Botswana. Design: Observational, single center. Setting: Academic, upper middle-income country. Subjects: Healthcare providers in Botswana. Interventions: A cohort of healthcare providers completed the standard 2-day Pediatric Fundamentals of Critical Care Support course and qualitative survey during the course. Cognitive knowledge was assessed prior to and immediately following training using standard Pediatric Fundamentals of Critical Care Support multiple choice questionnaires. Data analysis used Fisher exact, chi-square, paired t test, and Wilcoxon rank-sum where appropriate. Main Results: There was a significant increase in overall multiple choice questionnaires scores after training (mean 67% vs 77%; p < 0.001). Early career providers had significantly lower mean baseline scores (56% vs 71%; p < 0.01), greater knowledge acquisition (17% vs 7%; p < 0.02), but no difference in posttraining scores (73% vs 78%; p = 0.13) compared with more senior providers. Recent pediatric resuscitation or emergency training did not significantly impact baseline scores, posttraining scores, or decrease knowledge acquisition. Eighty-eight percent of providers perceived the course was highly relevant to their clinical practice, but only 71% reported the course equipment was similar to their current workplace. Conclusions: Pediatric Fundamentals of Critical Care Support training significantly increased provider knowledge to care for hospitalized seriously ill or injured children in Botswana. Knowledge accrual is most significant among early career providers and is not limited by previous pediatric resuscitation or emergency training. Further contextualization of the course to use equipment relevant to providers work environment may increase the value of training.